Determination of growth stages of some rice varieties as affected by sowing time (Bangladesh Rice Journal, 2023)
Identification of growth stages of rice is important for proper crop management and yield estimation. Appropriate planting time is a prerequisite for a decent harvest. The study aimed to determine the growth stages of different rice varieties and how they are affected by the sowing time. We evaluated four selected boro season rice varieties (BRRI dhan81, BRRI dhan86, BRRI dhan88, and BRRI dhan89) under five sowing times for growth stage study and yield following a completely randomized block design (RCBD) with three replications. Each variety showed considerable variation in different growth stages and yield at various sowing dates. All tested rice varieties took 40 days to reach the seedling stage on 15 December sowing.  With the advancement or preceding this sowing date, the days required to attain this stage decreased. In mid-November sowing, the maximum period (33-34 days) was needed for tiller development and then reduced with the advancement of sowing dates irrespective of variety.  Among the rice varieties, BRRI dhan89 required the highest time for panicle initiation (PI) on all sowing dates. The other three rice varieties took more or less similar time for panicle initiation. Among the rice varieties, BRRI dhan89 needed the highest, and BRRI dhan86 needed the lowest degree days for PI and flowering. BRRI dhan81 and BRRI dhan89 gave a higher grain yield from 15 November and  1 December sowing.  BRRI dhan88 produced consistent grain yield throughout the sowing time. The fluctuations in PI stages' commencement indicate varietal characteristics, environmental conditions, and interaction between variety and environment.Bangladesh Rice J. 26 (2): 41-49, 2022